REGULASI PEMBELAJARAN AL-ISLAM DAN KEMUHAMMADIYAHAN BAGI MAHASISWA NON-MUSLIM DI UNIVERSITAS MUHAMMADIYAH METRO - Siti Kisma Wati; Iswati; Heri Cahyono; Rika Amalia (Universitas Muhammadiyah Metro, 2026)
The regulations in Muhammadiyah universities are different from other universities. In terms of religious learning regulations, Muhammadiyah universities have AIK (Al-Islam and Kemuhammadiyahan) religious learning, which other universities do not have in the regulations for implementing religious learning for non-Muslim students in There is no Metro Muhammadiyah University, but there is a rectorate policy regarding Al-Islam and Muhammadiyahan standards that stipulates that all students at Metro Muhammadiyah University are obliged to take part in learning the religion of Al-Islam and Muhammadiyah so that there is compulsion on the part of non-Muslim students to take part in learning because this is a general compulsory course that must be taken. For the implementation of religious learning. This research aims to understand the regulations for implementing religious learning for non-Muslim students and the implementation of religious learning for non-Muslim students at Metro Muhammadiyah University, Lampung. The method used in this research is a qualitative method with a descriptive approach. Data collection techniques for this research use interview, observation, and documentation techniques. Data analysis for this research is carried out by data reduction, data display, verification, and drawing conclusions. The research findings state that the regulations for religious learning for non-Muslim students at Metro Muhammadiyah University are in accordance with the university's policy regarding standards for implementing al-Islam and Muhammadiyah learning, which requires all teachers. Implementing religious learning for non-Muslim students at Muhammadiyah Metro University requires them to take mandatory religious learning courses, namely al-Islam and Muhammadiyah, for eight credits from semesters I to IV. Inclusivity in the implementation of religious learning regulations for non-Muslim students has not been fulfilled according to government regulations; regulations for religious learning for non-Muslim students at Metro Muhammadiyah University do not yet exist, so the policy that has been used as a reference is the joint policy of the relevant Metro Muhammadiyah University rectorate religious learning for non-Muslim students. Efforts made by the university to provide solutions to the implementation of religious learning for non-Muslim students at Metro Muhammadiyah University by creating regulations for religious learning for non-Muslim students.